Expanding the spectrum of genes responsible for hereditary motor neuropathies. Issue 10 (5th June 2019) - Previtali, Stefano C.; Zhao, Edward; Lazarevic, Dejan; Pipitone, Giovanni Battista; Fabrizi, Gian Maria; Manganelli, Fiore; Mazzeo, Anna; Pareyson, Davide; Schenone, Angelo; Taroni, Franco; Vita, Giuseppe; Bellone, Emilia; et al.
Abstract : Background: Inherited peripheral neuropathies (IPNs) represent a broad group of genetically and clinically heterogeneous disorders, including axonal Charcot-Marie-Tooth type 2 (CMT2) and hereditary motor neuropathy (HMN). Approximately 60%–70% of cases with HMN/CMT2 still remain without a genetic diagnosis. Interestingly, mutations in HMN/CMT2 genes may also be responsible for motor neuron disorders or other neuromuscular diseases, suggesting a broad phenotypic spectrum of clinically and genetically related conditions. Thus, it is of paramount importance to identify novel causative variants in HMN/CMT2 patients to better predict clinical outcome and progression. Methods: We designed a collaborative study for the identification of variants responsible for HMN/CMT2. We collected 15 HMN/CMT2 families with evidence for autosomal recessive inheritance, who had tested negative for mutations in 94 known IPN genes, who underwent whole-exome sequencing (WES) analyses. Candidate genes identified by WES were sequenced in an additional cohort of 167 familial or sporadic HMN/CMT2 patients using next-generation sequencing (NGS) panel analysis. Results: Bioinformatic analyses led to the identification of novel or very rare variants in genes, which have not been previously associated with HMN/CMT2 ( ARHGEF28, KBTBD13, AGRN and GNE ); in genes previously associated with HMN/CMT2 but in combination with different clinical phenotypes ( VRK1 and PNKP ), and in the SIGMAR1 gene, which has been linked to HMN/CMT2 in only a few cases. These findings were further validated by Sanger sequencing, segregation analyses and functional studies. Conclusions: These results demonstrate the broad spectrum of clinical phenotypes that can be associated with a specific disease gene, as well as the complexity of the pathogenesis of neuromuscular disorders.